2013
DOI: 10.1007/s11427-013-4485-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of cancer-related polyadenylated and non-polyadenylated RNAs in human breast and lung cell lines

Abstract: Eukaryotic mRNAs consist of two forms of transcripts: poly(A)+ and poly(A), based on the presence or absence of poly(A) tails at the 3 end. Poly(A)+ mRNAs are mainly protein coding mRNAs, whereas the functions of poly(A) mRNA are largely unknown. Previous studies have shown that a significant proportion of gene transcripts are poly(A)or bimorphic (containing both poly(A)+ and poly(A) transcripts). We compared the expression levels of poly(A) and poly(A)+ RNA mRNAs in normal and cancer cell lines. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Inspired by the rapid and efficient response of both probes and based on the above platform, we further applied the contrary logic response to ratiometric fluorescent analysis of nucleic acids. It has been reported that poly-A tails can regulate the expression and stability of mRNA and is significant for the initiation of translation [54][55][56]. Therefore, the analysis of poly-A sequences could provide informative evidence for the early diagnosis of diseases.…”
Section: Ratiometric Fluorescent Detection Of Poly-a Strandmentioning
confidence: 99%
“…Inspired by the rapid and efficient response of both probes and based on the above platform, we further applied the contrary logic response to ratiometric fluorescent analysis of nucleic acids. It has been reported that poly-A tails can regulate the expression and stability of mRNA and is significant for the initiation of translation [54][55][56]. Therefore, the analysis of poly-A sequences could provide informative evidence for the early diagnosis of diseases.…”
Section: Ratiometric Fluorescent Detection Of Poly-a Strandmentioning
confidence: 99%
“…Furthermore, lncRNAs deregulation has been linked to a number of human illnesses, including cancer [ 21 ]. LncRNAs are single-stranded ncRNAs longer than 200 nucleotides which are transcribed by RNA polymerase II [ 21 , 23 , 24 ]. Several mechanisms such as serving as microRNAs sponges, signals, decoys, scaffolds, and guides, through which lncRNAs influence gene expression, have been postulated [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%